Family Functioning in the Time of COVID-19 Among Economically Vulnerable Families: Risks and Protective Factors - He, Minxuan; Cabrera, Natasha; Renteria, Jone; Chen, Yu; Alonso, Angelica; McDorman, S. Alexa; Kerlow, Marina A.; Reich, Stephanie M. (Frontiers in Psychology, 2021)
The ongoing COVID-19 crisis has been particularly harmful to economically vulnerable families with young children. We surveyed 247 low-income mothers and fathers from 142 families in the United States about changes in their family life following the economic and social restrictions imposed by the pandemic. We examined the associations between pandemic-related risk factors such as economic stressors (e.g., loss of job) and social stressors (e.g., exposure to the virus) on family functioning (e.g., parents’ mental health, parent engagement, and children’s socioemotional behaviors) and the degree to which coparenting support and parents’ positivity protected families from the negative effects of these stressors on their wellbeing. We found both positive and negative associations. Mothers and fathers who reported more economic stressors since the pandemic also observed that their children behaved more prosocially and that fathers experienced more mental health difficulties during the pandemic. Mothers and fathers who reported more social stressors reported that they were less engaged with their children and their children exhibited more behavior problems compared to before the pandemic. We also found that mothers and fathers who reported feeling more positive also reported feeling less depressed and stressed during the pandemic and observed that their children had more prosocial behaviors compared to before the pandemic. Compared to before the pandemic, mothers and fathers who reported a more supportive coparenting relationship also reported more parent engagement and observed more prosocial behaviors in their children. In terms of protective factors, high levels of parent positivity during the pandemic protected mothers (less mental health difficulties) whereas high levels of coparenting support protected fathers (less mental health difficulties) from the negative effects of economic stress on their mental health during the pandemic. These findings highlight family processes that could promote resilience in mothers and fathers in the face of pandemic-related economic and social stressors.